2021
DOI: 10.3390/cimb43030087
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Oligopeptides Mimicking γ-Core Regions of Cysteine-Rich Peptides of Solanum lycopersicum Possess Antimicrobial Activity against Human and Plant Pathogens

Abstract: Plant cysteine-rich peptides (CRPs) represent a diverse group of molecules involved in different aspects of plant physiology. Antimicrobial peptides, which directly suppress the growth of pathogens, are regarded as promising templates for the development of next-generation pharmaceuticals and ecologically friendly plant disease control agents. Their oligopeptide fragments are even more promising because of their low production costs. The goal of this work was to explore the antimicrobial activity of nine short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Structure–function studies of the classical defensins showed that the antimicrobial activity is associated, at least in part, with their γ-core motifs [ 17 , 30 ]. In our studies of tomato CRPs, we showed that the γ-core motifs of the CRPs belonging to other peptide families, such as snakins, MEG (Maternally Expressed Gene) peptides, and nsLTPs, also possess antimicrobial activity [ 18 ]. However, it remained unclear as to whether the γ-cores of the so-called 4-Cys DEFLs, knottin- and thionin-like peptides display antimicrobial properties.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Structure–function studies of the classical defensins showed that the antimicrobial activity is associated, at least in part, with their γ-core motifs [ 17 , 30 ]. In our studies of tomato CRPs, we showed that the γ-core motifs of the CRPs belonging to other peptide families, such as snakins, MEG (Maternally Expressed Gene) peptides, and nsLTPs, also possess antimicrobial activity [ 18 ]. However, it remained unclear as to whether the γ-cores of the so-called 4-Cys DEFLs, knottin- and thionin-like peptides display antimicrobial properties.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the production and storage of cultures of microorganisms used in this study are described at the VKM Home page [ 45 ]. Antimicrobial assays were accomplished according to the procedure described earlier [ 18 ]. In short, yeasts were grown on the YPD-P medium and the bacteria P. carotovorum and Cl.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations